Determinants of E-Money Transactions in ASEAN and G20 Countries: A Panel Data Analysis: Faktor-Faktor Penentu Transaksi Uang Elektronik di Negara-Negara ASEAN dan G20: Analisis Data Panel - Fischa Syafira Ayu; Nairobi, Nairobi; Taher, Arivina Ratih (Jurnal Bisnis dan Ekonomi, 2026)
Abstrak : Objective : ASEAN and the G20 are two international cooperation forums that differ in their institutional structures and scopes of roles, yet both hold significant importance in maintaining economic and political stability. Methodology : ASEAN emphasizes the strengthening of regional integration in Southeast Asia through consensus-based decision-making mechanisms and the principle of non-intervention, whereas the G20 serves as a platform for global economic coordination without a permanent secretariat. Research results : This study aims to examine the similarities and differences between the two forums, particularly with regard to their formation, operational mechanisms, and contributions to economic stability. The study employs a descriptive qualitative approach using a literature review method. The findings indicate that ASEAN’s effectiveness is largely grounded in normative consistency and the formation of regional identity, while the G20’s performance is strongly influenced by macroeconomic policy coordination and the speed of its response to global crises. This study is expected to contribute to and enrich the literature on multilateral economic governance. Keyword: Asean, G20, Economic Governance, Economic Stability.